2024
DOI: 10.3847/1538-3881/ad28bb
|View full text |Cite
|
Sign up to set email alerts
|

The TESS-Keck Survey. XII. A Dense 1.8 R Ultra-short-period Planet Possibly Clinging to a High-mean-molecular-weight Atmosphere after the First Gigayear

Ryan A. Rubenzahl,
Fei Dai,
Andrew W. Howard
et al.

Abstract: The extreme environments of ultra-short-period planets (USPs) make excellent laboratories to study how exoplanets obtain, lose, retain, and/or regain gaseous atmospheres. We present the confirmation and characterization of the USP TOI-1347 b, a 1.8 ± 0.1 R ⊕ planet on a 0.85 day orbit that was detected with photometry from the TESS mission. We measured radial velocities of the TOI-1347 system using Keck/HIRES and HARPS-N and found the USP to be unusually massive at 11.1 ± 1.2 M … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…Weiss & Marcy (2014) posited that these two regimes of the M-R parameter space may be separated by a threshold radius R cut ≈ 1.5 R ⊕ , while Rogers (2015) determined via a hierarchical Bayesian framework that this boundary may instead lie closer to R cut ≈ 1.6 R ⊕ , a value that has since been corroborated by recent empirical fitting of expanded planetary catalogs (Lozovsky et al 2018;Baron et al 2023). Furthermore, it has been shown that extant precise (δM p /M p  0.3) mass measurements for rocky worlds with R cut 1.6 R ⊕ yield exceptionally close agreement (Rodríguez Martínez et al 2023;Rubenzahl et al 2024) with the semi-empirical M-R relation for Earth-composition (30% Fe, 70% MgSiO 3 ) planets presented by Zeng et al (2016). As such, we adopt hereafter this R cut = 1.6 R ⊕ threshold as the basis for classification of rocky and volatile-rich worlds throughout this analysis.…”
Section: Compositional Classification Schemementioning
confidence: 99%
See 2 more Smart Citations
“…Weiss & Marcy (2014) posited that these two regimes of the M-R parameter space may be separated by a threshold radius R cut ≈ 1.5 R ⊕ , while Rogers (2015) determined via a hierarchical Bayesian framework that this boundary may instead lie closer to R cut ≈ 1.6 R ⊕ , a value that has since been corroborated by recent empirical fitting of expanded planetary catalogs (Lozovsky et al 2018;Baron et al 2023). Furthermore, it has been shown that extant precise (δM p /M p  0.3) mass measurements for rocky worlds with R cut 1.6 R ⊕ yield exceptionally close agreement (Rodríguez Martínez et al 2023;Rubenzahl et al 2024) with the semi-empirical M-R relation for Earth-composition (30% Fe, 70% MgSiO 3 ) planets presented by Zeng et al (2016). As such, we adopt hereafter this R cut = 1.6 R ⊕ threshold as the basis for classification of rocky and volatile-rich worlds throughout this analysis.…”
Section: Compositional Classification Schemementioning
confidence: 99%
“…constituent planets, indicating that these CKS samples lack the requisite associated planetary mass data for a population-level uniformity analysis. However, this dearth may be alleviated in part by the substantial efficacy with which the M-R bivariate behavior of small, rocky (R p 1.6 R ⊕ ) worlds may be modeled (see Figure 5 of Rodríguez Martínez et al 2023; Figure 8 of Rubenzahl et al 2024) by the semi-empirical M-R relation for Earth-like planets presented by Zeng et al (2016). We therefore utilize this Zeng et al (2016) Earth-composition model to robustly infer planetary masses M p for the 118 objects (across 48 systems) within our CKS rocky sample (Figure 3, gold curve and points).…”
Section: Inference Of Planetary Masses For Cks Rocky Systemsmentioning
confidence: 99%
See 1 more Smart Citation